A Dynamic Platform for Developing 3D Facial Avatars in a Networked Virtual Environment - Anis Zarrad (International Journal of Computer Games Technology)
Avatar facial expression and animation in 3D collaborative virtual environment (CVE) systems are reconstructed through a complex manipulation of muscles, bones, and wrinkles in 3D space. The need for a fast and easy reconstruction approach has emerged in the recent years due to its application in various domains: 3D disaster management, virtual shopping, and military training. In this work we proposed a new script language based on atomic parametric action to easily produce real-time facial animation. To minimize use of the game engine, we introduced script-based component where the user introduces simple short script fragments to feed the engine with a new animation on the fly. During runtime, when an embedded animation is required, an xml file is created and injected into the game engine without stopping or restarting the engine. The resulting animation method preserves the real-time performance because the modification occurs not through the modification of the 3D code that describes the CVE and its objects but rather through modification of the action scenario that rules when an animation happens or might happen in that specific situation.